2016
DOI: 10.1016/j.cortex.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset and late-onset Alzheimer's disease are associated with distinct patterns of memory impairment

Abstract: The goal of this study was to investigate the specific patterns of memory breakdown in patients suffering from early-onset Alzheimer's disease (EOAD) and late-onset Alzheimer's disease (LOAD). Twenty EOAD patients, twenty LOAD patients, twenty matched younger controls, and twenty matched older controls participated in this study.All participants underwent a detailed neuropsychological assessment, an MRI scan, an FDG-PET scan, and AD patients had biomarkers as supporting evidence of both amyloïdopathy and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 91 publications
(120 reference statements)
6
66
0
4
Order By: Relevance
“…EOAD, compared to LOAD, presents less commonly with memory deficits and more frequently as focal cortical or phenotypic variants (described below) 25 . Overall, EOAD patients, compared to comparably impaired LOAD patients, have better memory recognition scores and semantic memory 26 , but they tend to have worse attention, executive functions, ideomotor praxis, and visuospatial skills 25,26 . On magnetic resonance imaging (MRI), EOAD shows greater neocortical atrophy, particularly in parietal cortex, with less atrophy in the mesial temporal lobe (MTL) 27,28 .…”
Section: Introductionmentioning
confidence: 94%
“…EOAD, compared to LOAD, presents less commonly with memory deficits and more frequently as focal cortical or phenotypic variants (described below) 25 . Overall, EOAD patients, compared to comparably impaired LOAD patients, have better memory recognition scores and semantic memory 26 , but they tend to have worse attention, executive functions, ideomotor praxis, and visuospatial skills 25,26 . On magnetic resonance imaging (MRI), EOAD shows greater neocortical atrophy, particularly in parietal cortex, with less atrophy in the mesial temporal lobe (MTL) 27,28 .…”
Section: Introductionmentioning
confidence: 94%
“…Copying tasks are, therefore, substantially spared in degenerative diseases mainly involving the frontal (bvFTD) or temporal (SD) cortices and might be mildly impaired in the early stages of standard forms of AD, in which atrophy prevails in the medial temporal lobes, although neuroimaging studies repeatedly showed a pattern of reduced metabolism in the temporo-parietal areas [204,205]. A much more severe impairment in copying tasks is observed in early-onset AD patients and in PCA variant, in which severe constructive defects are usually associated with progressive visual-spatial disorders, including Balint syndrome and unilateral spatial neglect [100,101]. A very similar pattern of drawing impairment is found in LBD, in which visuospatial difficulties are often early and prominent and contribute to the disproportionate impairment in constructional tasks observed in these patients [151][152][153].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have, therefore, examined the relations between age at onset and drawing disorders in AD patients, and reported a high prevalence of visuoconstructional disabilities, assessed with the copy of the ROCF, in EOAD patients [101][102][103]. In some studies [102,103], but not in others [101], these drawing disorders were associated with visuospatial deficits. Furthermore, some studies [104] have shown that the presence and severity of drawing disorders certainly depends on the AD phenotype and not just on age.…”
Section: Drawing Disabilities In Early and Late Onset Forms Of Admentioning
confidence: 99%
See 1 more Smart Citation
“…У нашей пациентки симптоматика также прогрессирует достаточно быстро (за 2-3 года когнитивный дефицит достиг стадии умеренной деменции). При БАсРН, по сравнению с БА с поздним дебютом, реже встречается дефицит памяти, пациенты с БАсРН отличаются более выраженными нарушениями внимания, исполнительных функций, идеомоторного праксиса и визуально-пространственных функций [7,8]. У нашей пациентки имеющийся несомненный мнестический дефект отходит на второй план на фоне грубых нарушений праксиса, письма, счета и речи.…”
Section: Discussionunclassified